CONFLICT IN MICHELLE ZAUNER’S NOVEL CRYING IN H MART: A MEMO - Novia Mentari; Safitri Hariani (Universitas Islam Sumatera Utara, 2023)
This study analyzes a novel by Michelle Zauner entitled Crying in H Mart: A Memoir. This research focuses on the conflicts that occur to the protagonist, Michelle Zauner. The purpose of this study is to reveal the external and internal conflicts that occur in the novel. The researchers applied descriptive qualitative approach to conduct this research. The descriptive approach means that the data collected is in the form of notes or memos, personal documents, or other official documents. Also, the researchers use the conflict theory described by several experts, such as Stanton, Sayuti, and Nurgiyantoro as a reference for discussion, so that the topic under study runs systematically. For the analysis, it is found that the protagonist in the novel experienced both external and internal conflicts. The external conflicts that occur to Michelle are the difficulty of being mixed-blood and disputes with her father. The internal conflicts occur in the novel due to sadness of her mother's illness and death, and pressure of future dreams.